Use of digital technologies to optimise the supply of construction materials and equipment - Chubin, A (Ways to Improve Construction Efficiency, 2024)
In the context of increasing project complexity, shorter implementation timelines, and external challenges such as global disruptions in supply chains, the application of digital technologies has become a necessary condition for ensuring the stability and competitiveness of construction enterprises. The relevance of the study lies in the need to overcome the limitations of traditional supply models, which often lack transparency, are characterized by poor coordination among stakeholders, and are vulnerable to delays and resource losses. The aim of the article is to examine the capabilities and impact of digital technologies on optimizing supply processes in construction, particularly the use of integrated platforms, real-time tracking systems, data analytics, and automation tools. The study analyzes practical cases of digital technology implementation in both Ukrainian and international contexts, showing how technologies such as Building Information Modeling (BIM), the Internet of Things (IoT), cloud-based solutions, and artificial intelligence contribute to improving delivery accuracy, cost control, and flexibility of logistics decisions. The results of the study showed that the implementation of digital tools leads to a significant increase in supply chain efficiency, a reduction in material losses and transportation costs, as well as greater resilience of construction operations in a dynamically changing environment. It is emphasized that the adoption of modern digital technologies will not only optimize the supply of construction materials and equipment but also modernize the entire industry. The conclusions highlight that the digitalization of construction logistics is not only a technological upgrade but also a strategic transformation that requires organizational change, staff training, and the development of a supportive institutional framework. Ensuring successful implementation depends on a comprehensive approach that integrates technological innovation with new supply chain management models and industry-wide collaboration.